(untitled) (Fiep Bulletin - online, 2013)
Exploratory descriptive study, quantitative with prospective data performed on Monsenhor Walfredo Gurgel hospital complex, in Natal/RN, aiming to characterize the victims involved on traffic accidents according to sex, age group, use of personal protection equipment and its relation with the severity of injuries; to identify the injuries by body region according to the type of public road user. The population consisted of 605 traffic accident victims and the data was collected between November and December 2007 and January 2008. The results show us that 82.8% of victims were male, 37.9% subjects were between 18 and 24 years, and the relationship between the use of PPE and severity of injuries, it was observed that 53.4% victims used PPE, and the helmet was used in 49.4% of cases. This population, 7.8% of the victims had values for ECGl between 3 and 8 points (bass) and 9.2%, between 9 and 12 (moderate). When compared to those who have used PPE, only 0.9% had values for ECGl between 3 and 8 (severe). As for physical injuries by region according to the user of public roads, identified that a total of 1645 anatomical lesions, 35.9% occurred on the external surface, which is the region most affected by injuries, and 35.3% in the region head / neck. The driver of the motorcycle was kind of victim who suffered more injuries, 57.1% in virtually all segments tangible. The results show us that it’s necessary to recognize the importance of the adoption of regulation measures for the use of PPE, the adoption of adequate behavior towards traffic, as well as a monitoring policy towards the following of rules related to traffic.